2021
DOI: 10.13189/saj.2021.090637
|View full text |Cite
|
Sign up to set email alerts
|

Tennis Home-Training during First Italy Lockdown COVID-19: A Pilot Study in Young Athletes

Abstract: COVID-19 pandemic has imposed an Italy national lockdown between 9 March and 3 May 2020, limiting the ability of individuals to exercise/training outdoors. The aim of this study was based on the construction of remote-personalized-training protocols in tennis and examined the effects of a home-based intervention. Sixteen young athletes, divided into four groups in accord with the level of play and the pre-existing technical-tactical preparation, were trained by tennis-coach using simple equipment (i.e., balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…In addition to those studies that observed impairments in squat and countermovement jump performance induced by the pandemic, some studies have found no significant changes associated with the occurrence of COVID-19 [17]. Moreover, in accordance with our findings, there are also studies showing the positive effects of home training during lockdown on jump performance in soccer players [38] and young tennis players [39]. This could support the increase in jump height observed in our study, as the specific change in training practices adopted by our participants may have induced a training stimulus conducive to increases in lower-limb power.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to those studies that observed impairments in squat and countermovement jump performance induced by the pandemic, some studies have found no significant changes associated with the occurrence of COVID-19 [17]. Moreover, in accordance with our findings, there are also studies showing the positive effects of home training during lockdown on jump performance in soccer players [38] and young tennis players [39]. This could support the increase in jump height observed in our study, as the specific change in training practices adopted by our participants may have induced a training stimulus conducive to increases in lower-limb power.…”
Section: Discussionsupporting
confidence: 90%